Pelatihan Dasar Akuntansi Digital: Menyiapkan Generasi Muda Menghadapi Transformasi Profesi Akuntan - Endah Tri Wahyuningtyas; Lalu Muhammad Syahril Majidi; Salamatul Insan Suhari; M. Fahri; Alfi Lailatul Fitriyah (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity is carried out to increase knowledge about the basic basics of accounting that must be understood for prospective accountants in MA Muallimien Darul Ittihad Madura students. Therefore, the delivery of material related to the basis of accounting is made with a method that is easy to understand. In addition, students are also given a pre-test and pro-test to determine the comparison between knowledge before assistance and increased knowledge after this activity is carried out. This assistance began with material presentation activities and continued with discussion sessions. The increase in the results of the pre-test and post-test comparison of this assistance can be said that this activity has a positive impact on MA Muallimien Darul Ittihad Madura students.